On civil procedure / J.A. Jolowicz. - Jolowicz, J. A. (John Anthony) (Cambridge studies in international and comparative law (Cambridge, England : 1996) ;, 2000)
Professor Jolowicz's comparative analysis of civil procedure concentrates on the purposes served by the institution of litigation rather than on the intentions of those who litigate. Stressing that those purposes go beyond mere dispute resolution by non-violent means, Jolowicz surveys a variety of topics of procedural law, making substantial use of the comparative method, in the attempt to examine and explain the ideas which underlie some of the most important of its constituent elements. In the final section, he deals with the reform of English law and ventures a prediction of the consequences that the new Civil Procedure Rules, together with the reforms which more or less immediately preceded them, will have on the character of English procedural law.